Non‐canonical structure, function and phylogeny of the Bsister MADS‐box gene OsMADS30 of rice (Oryza sativa). (7th December 2015) - Schilling, Susanne; Gramzow, Lydia; Lobbes, Dajana; Kirbis, Alexander; Weilandt, Lisa; Hoffmeier, Andrea; Junker, Astrid; Weigelt‐Fischer, Kathleen; Klukas, Christian; Wu, Feng; Meng, Zheng; Altmann, Thomas; et al.
Summary: Bsister MADS‐box genes play key roles in female reproductive organ and seed development throughout seed plants. This view is supported by their high conservation in terms of sequence, expression and function. In grasses, there are three subclades of Bsister genes: the OsMADS29 ‐, the OsMADS30 ‐ and the OsMADS31 ‐like genes. Here, we report on the evolution of the OsMADS30 ‐like genes. Our analyses indicate that these genes evolved under relaxed purifying selection and are rather weakly expressed. OsMADS30, the representative of the OsMADS30 ‐like genes from rice ( Oryza sativa ), shows strong sequence deviations in its 3′ region when compared to orthologues from other grass species. We show that this is due to a 2.4‐kbp insertion, possibly of a hitherto unknown helitron, which confers a heterologous C‐terminal domain to OsMADS30 . This putative helitron is not present in the OsMADS30 orthologues from closely related wild rice species, pointing to a relatively recent insertion event. Unlike other Bsister mutants O. sativa plants carrying a T‐DNA insertion in the OsMADS30 gene do not show aberrant seed phenotypes, indicating that OsMADS30 likely does not have a canonical 'Bsister function'. However, imaging‐based phenotyping of the T‐DNA carrying plants revealed alterations in shoot size and architecture. We hypothesize that sequence deviations that accumulated during a period of relaxed selection in the gene lineage that led to OsMADS30 and the alteration of the C‐terminal domain might have been a precondition for a potential neo‐functionalization of OsMADS30 in O. sativa . Significance Statement: Gene duplications can lead to neo‐functionalization or sub‐functionalization of one duplicate. Bsister genes are highly conserved MADS‐box genes involved in ovule and seed development. Here we present molecular phylogenetic analysis of OsMADS30 ‐like Bsister genes from monocots, suggesting that many evolved under relaxed selection. Surprisingly, relaxed selection might have facilitated neo‐functionalization for OsMADS30, whose mutant shows an unexpected vegetative phenotype.